2021
DOI: 10.1111/ejn.15446
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with dropout in the longitudinal Vogel study of cognitive decline

Abstract: Dementia, including Alzheimer's disease, is a growing problem worldwide.Prevention or early detection of the disease or a prodromal cognitive decline is necessary. By means of our long-term follow-up 'Vogel study', we aim to predict the pathological cognitive decline of a German cohort (mean age was 73.9 AE 1.55 years at first visit) with three measurement time points within 6 years per participant. Especially in samples of the elderly and subjects with chronic or co-morbid diseases, dropouts are one of the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…This finding suggests that long‐term follow‐up studies may bias towards healthier subjects. These factors must therefore be considered in the interpretation of completed or ongoing studies and in the development of strategies to maximize retention in future studies (Haberstumpf et al, 2021). Foxe et al investigated the evolution of deficits in behaviour, mood and functional capacity in a longitudinal study of 145 individuals with variants of primary progressive aphasia.…”
Section: Clinical Research and Biomarkersmentioning
confidence: 99%
“…This finding suggests that long‐term follow‐up studies may bias towards healthier subjects. These factors must therefore be considered in the interpretation of completed or ongoing studies and in the development of strategies to maximize retention in future studies (Haberstumpf et al, 2021). Foxe et al investigated the evolution of deficits in behaviour, mood and functional capacity in a longitudinal study of 145 individuals with variants of primary progressive aphasia.…”
Section: Clinical Research and Biomarkersmentioning
confidence: 99%
“…1,2 While it is a devastating disease for our society, Alzheimer dementia has a long prodromal phase, providing a critical time window for potential interventions to successfully postpone or prevent the disease's onset. 3,4 Therefore, it is a public health priority to identify people at very early stages of cognitive impairment and consequently to prevent or postpone neurodegenerative diseases. 5 In recent years, a growing body of research has shown that individuals with no evident objective cognitive impairment but who demonstrate concerns about everyday memory, known as subjective memory complaints (SMCs), are at high risk of faster cognitive decline and developing incident dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer dementia, a progressive brain disorder that impairs memory, thinking, and decision-making abilities, is a leading cause of disability in a growing aging population . While it is a devastating disease for our society, Alzheimer dementia has a long prodromal phase, providing a critical time window for potential interventions to successfully postpone or prevent the disease’s onset . Therefore, it is a public health priority to identify people at very early stages of cognitive impairment and consequently to prevent or postpone neurodegenerative diseases …”
Section: Introductionmentioning
confidence: 99%